Implementation of a checklist to enhance operation note quality at a UK burns centre. Issue 4 (June 2019) - Khajuria, Ankur; Charles, Walton; Williams, Andrew; Leon-Villapalos, Jorge; Atkins, Joanne; Jones, Isabel; Bache, Sarah; Collins, Declan
Highlights: No national guidelines for completing burns operation notes currently exist. We designed a burns surgery-specific checklist to improve operation note quality. Post-intervention compliance significantly improved in all but 1 of 22 fields. A checklist represents a simple and cheap method to improve note quality. Abstract: Introduction: Operation notes are fundamental for clinical, academic and medico-legal purposes. Good Surgical Practice (2014) provides guidelines to assist note completion but the literature suggests poor adherence to these. The aim of this study was to evaluate and improve operation note quality at a UK burns centre through implementation of a burns surgery-specific checklist. Methods: A 22-component burns surgery-specific checklist, modified from Good Surgical Practice (2014), was designed and implemented. The quality of 80 operation notes (40 pre and 40 post-implementation) was assessed against this checklist. Fisher's exact and Mann-Whitney U statistical tests were used to evaluate pre and post-intervention note quality. Results: Before checklist implementation, only 6/22 components (27.3%) were recorded on every note. 4/22 components (18.2%) were not recorded on any, including microbiology specimen and clinical photography, which are particularly important in burns. After implementation, 16/22 (72.7%) were recorded on every note, with a statistically significant improvement in all other components (p ≤ 0.01), except venous thromboembolism prophylaxis (p = 0.10). The median percentage score of components recorded improved from 78.2 to 100% (p < 0.01). Conclusion: To our knowledge, this is the first study in available literature to show that a burns surgery-specific checklist can significantly improve burns operation note quality. This presents a simple and cheap method to improve note quality and may enhance post-operative intra/inter-team communication and patient care. At our unit, we have now developed an electronic checklist format with mandatory field completion to facilitate total compliance.